Wnt Inhibitory Factor 1 Deficiency Uncouples Cartilage and Bone Destruction in Tumor Necrosis Factor α–Mediated Experimental Arthritis. Issue 9 (26th August 2013) - Stock, Michael; Böhm, Christina; Scholtysek, Carina; Englbrecht, Matthias; Fürnrohr, Barbara G.; Klinger, Patricia; Gelse, Kolja; Gayetskyy, Svitlana; Engelke, Klaus; Billmeier, Ulrike; Wirtz, Stefan; van den Berg, Wim; et al.
<x xml:space="preserve">Abstract</x> Objective Wnt signaling plays a pivotal role in skeletal development and in the control of cartilage and bone turnover. We have recently shown that the secreted Wnt antagonist Wnt inhibitory factor 1 (WIF‐1) is mainly expressed in the upper layers of epiphyseal and articular cartilage and, to a lesser extent, in bone. Nevertheless, WIF‐1−/− mice develop normally. In light of these findings, we undertook this study to analyze the role of WIF‐1 in arthritis. Methods Expression analyses for WIF‐1 were performed by real‐time reverse transcription–polymerase chain reaction (RT‐PCR). WIF‐1−/− and tumor necrosis factor (TNF)–transgenic mice were crossbred, and the progression of arthritis in TNF‐transgenic WIF‐1−/− mice and littermate controls was evaluated. Structural joint damage was analyzed by histologic staining, histomorphometry, and micro–computed tomography. Wnt/β‐catenin signaling was investigated by real‐time RT‐PCR and immunofluorescence on primary chondrocytes. Results WIF‐1 expression was repressed by TNFα in chondrocytes and osteoblasts and down‐regulated in experimental arthritis and in articular cartilage from patients with rheumatoid arthritis. WIF‐1 deficiency partially protected TNF‐transgenic mice against bone erosion and loss of trabecular bone, probably as a result of less osteoclast activity. In contrast, arthritis‐related cartilage damage was aggravated by WIF‐1 deficiency, while overexpression of WIF‐1 attenuated cartilage degradation in TNF‐transgenic mice. In chondrocytes, TNFα stimulated canonical Wnt signaling, which could be blocked by WIF‐1, indicating a direct effect of TNFα and WIF‐1 on Wnt signaling in this system. Conclusion These data suggest that WIF‐1 may take part in the fine‐tuning of cartilage and bone turnover, promoting the balance of cartilage versus bone anabolism.